2016
DOI: 10.3109/09273948.2015.1134581
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab for Ocular Inflammation

Abstract: Purpose To evaluate adalimumab as an immunomodulatory treatment for non-infectious ocular inflammatory diseases. Methods Characteristics of patients treated with adalimumab were abstracted in a standardized chart review. Main outcomes measured were control of inflammation, corticosteroid-sparing effect, and visual acuity. Results In total, 32 patients with ocular inflammation were treated with adalimumab. The most common ophthalmic diagnoses were anterior uveitis, occurring in 15 patients (47%), and scleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 21 publications
(16 reference statements)
1
25
1
Order By: Relevance
“…In a large prospective study of 131 patients on adalimumab for uveitis, visual acuity remained stable in 75.4% of eyes (n=113) after 6 months 19. Durrani et al 20 reported no significant change in visual acuity after 3–6 months of adalimumab therapy in 32 patients with ocular inflammatory disease, and Arcinue et al 21 reported similar results at 1 year in an equally heterogeneous group of 49 patients. In contrast, Bawazeer et al 22 published a series of 21 eyes with ocular Behçet’s disease, in which 81% had an improvement of visual acuity by three or more lines (average 4.33 lines) after 10 months of follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…In a large prospective study of 131 patients on adalimumab for uveitis, visual acuity remained stable in 75.4% of eyes (n=113) after 6 months 19. Durrani et al 20 reported no significant change in visual acuity after 3–6 months of adalimumab therapy in 32 patients with ocular inflammatory disease, and Arcinue et al 21 reported similar results at 1 year in an equally heterogeneous group of 49 patients. In contrast, Bawazeer et al 22 published a series of 21 eyes with ocular Behçet’s disease, in which 81% had an improvement of visual acuity by three or more lines (average 4.33 lines) after 10 months of follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…; Vallet et al. ; Durrani et al ) and the capability to rapidly reach therapeutic drug levels in the eye when used intravitreally (Modorati & Miserocchi ). One reason that may explain the lack of efficacy or long‐term efficacy in some of the studies is that their mechanisms of action may not be effective when administered locally in the eye, given the systemic nature of the diseases underlying the inflammatory process (Suhler et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although not formally approved for NIU, there are an important number of studies with infliximab specifically in two underlying conditions: Behc ßet disease and juvenile idiopathic arthritis (Levy-Clarke et al 2014;Cordero-Coma & Sobrin 2015). Moreover, evidence of the efficacy and safety of adalimumab and infliximab in adult NIU may also be found in case reports (Leccese et al 2011;Takase et al 2011;Zmuda et al 2013;Capote et al 2014;Ermetcan et al 2014;Achille et al 2016;Sakurai et al 2016), retrospective case series (Mushtaq et al 2007;Sobrin et al 2007;Handa et al 2011;Okada et al 2012;Al Rashidi et al 2013;Dobner et al 2013;Alfawaz et al 2014;van Denderen et al 2014;Interlandi et al 2014;Kruh et al 2014;Takeuchi et al 2014;Kim et al 2016;Vallet et al 2016;Durrani et al 2017) and prospective case series (Joseph et al 2003;Diaz-Llopis et al 2008;Rudwaleit et al 2009;Suhler et al 2009Suhler et al , 2013D ıaz-Llopis et al 2012;Erckens et al 2012).…”
Section: Rationale For Intravitreal Administration Of Anti-tnf Drugsmentioning
confidence: 97%
See 1 more Smart Citation
“…Because of the risk of recurrent demyelination episodes, TNFα inhibitors are contraindicated in patients with known demyelinating disease. Eye-care practitioners need to consider excluding demyelinating disease 29 Adalimumab Orbital sarcoid-like granuloma 1 30 Extraocular muscles Adalimumab Extraocular muscle swelling 1 31 Etanercept Ocular myositis 2 32,33 Conjunctiva Etanercept Squamous cell carcinoma 1 34 Sclera Etanercept Scleritis 8 13,35 Infliximab Scleritis 1 13 Cornea Adalimumab Herpes zoster keratitis (reactivation) 1 36…”
Section: Demyelinationmentioning
confidence: 99%